2019
DOI: 10.24820/ark.5550190.p010.826
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and reactivity of new dihydroisoquinoline-derived oxaziridines

Abstract: N-Alkyl oxaziridines react as oxygenating reagents in the presence of a nucleophile. In this work, we describe the synthesis of new dihydroisoquinoline oxaziridines, and their reactivity in an acid-promoted reaction both in presence and in absence of sulfides. In the absence of sulfides, a new nitrone is produced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The authors extended their study via incorporation of −NO 2 group in the aromatic ring of 22 to synthesize 25 via 24 . The synthesized compounds ( 25 ) were employed to oxidize sulfides [26,27] . It was revealed that due to the presence of trichloromethyl ( 23 ) and nitro groups ( 25 ) on the dihydroisoquinoline skeleton, the oxaziridine became more electrophilic and the reaction of oxygen transfer into sulphide occured in absence of acid (see section 3.1.2).…”
Section: Direct Synthesis Of Oxaziridinesmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors extended their study via incorporation of −NO 2 group in the aromatic ring of 22 to synthesize 25 via 24 . The synthesized compounds ( 25 ) were employed to oxidize sulfides [26,27] . It was revealed that due to the presence of trichloromethyl ( 23 ) and nitro groups ( 25 ) on the dihydroisoquinoline skeleton, the oxaziridine became more electrophilic and the reaction of oxygen transfer into sulphide occured in absence of acid (see section 3.1.2).…”
Section: Direct Synthesis Of Oxaziridinesmentioning
confidence: 99%
“…Consequently, it was reported that the presence of p ‐chlorophenyl group and two nitro groups on the dihydroisoquinoline skeleton ( 91 c and 91 d ) made oxaziridine more electrophilic and led to good sulfoxide conversion from sulfide 88 in short time (15 min and 5 min). Interestingly, the unsubstituted oxaziridines ( 91 a and 91 b ) yielded corresponding nitrones 93 quantitatively (Scheme 23b) [27] . The different substituents at positions 1 and 7 on the dihydroisoquinoline skeleton were primarily responsible for the formation of sulfoxides/nitrones via the oxidation of oxaziridines.…”
Section: Reactivities Of Oxaziridinesmentioning
confidence: 99%
See 1 more Smart Citation